Prevalence of class I–III BRAF mutations among 114, 662 cancer patients in a large genomic database. Issue 1 (January 2021) - Owsley, Jeff; Stein, Matthew K; Porter, Jason; In, Gino K; Salem, Mohamed; O'Day, Steven; Elliott, Andrew; Poorman, Kelsey; Gibney, Geoffrey; VanderWalde, Ari
BRAF mutations are relatively common in many cancers, particularly melanoma, colorectal cancer, and thyroid cancer and to a lesser extent in lung cancer. These mutations can be targeted by BRAF and MEK inhibitors, which exhibit good clinical activity. There are conflicting reports of the various relative rates of BRAF Class I mutations (V600 locus), defined as those that exhibit extremely strong kinase activity by stimulating monomeric activation of BRAF, Class II, define as non-V600 mutations that activate BRAF to signal as a RAS-independent dimer, and Class III mutations, defined as "kinase-dead" with low kinase activity as compared to wild type BRAF. Prospective studies have largely focused on patients with tumors harboring Class I BRAF mutations (limited to the V600 locus) where response rates up to 70% with BRAF plus MEK inhibition have been demonstrated. We report on the relative prevalence of various types of BRAF mutations across human cancers in a cohort of 114, 662 patients that received comprehensive genomic profiling using next-generation sequencing. Of these patients, 4517 (3.9%) a pathogenic or presumed pathogenic BRAF mutation (3.9%). Of these, 1271 were seen in melanoma, representing 39.7% of all melanomas sequenced, representing the highest rate in all tumors. Class I (V600) mutations were seen overall in 2841 patients (62.1% of BRAF mutations, 2.4% of total cancers). Class II mutations were seen in 746 tumors (16.5% of BRAF mutant, 0.7% of total), and Class III mutations were seen in 801 tumors (17.7% of BRAF, 0.7% of total). Knowledge of the relative prevalence of these types of mutations can aid in the development of agents that might better address non-V600 mutations in cancer. Impact statement: These data represent the largest aggregation of BRAF mutations within a single clinical database to our knowledge. The relative proportions of both BRAF V600 mutations and non-V600 mutations are informative in all cancers and by malignancy, and can serve as a definitive gold-standard for BRAF mutation cancer incidence by malignancy. The rate of BRAF mutation in human cancer in a real-world large database is lower than previously reported likely representing testing more broadly across tumor types. The relative percentages of Class II and Class III BRAF mutations are higher than previously reported, representing almost 35% of BRAF mutations in cancer. These findings provide support for the development of effective treatments for non-V600 BRAF mutations in cancer.